2021
DOI: 10.1097/md.0000000000027596
|View full text |Cite
|
Sign up to set email alerts
|

Managing social anxiety among undergraduate adult education and extra-mural studies students

Abstract: Background/Objective: Anxiety is a significant problem affecting University students including undergraduate adult education and extra-mural studies students. This research evaluated the impact of a group rational-emotive behavioral education intervention (group rational-emotive behavioral education intervention [REBEI]) on social anxiety symptoms among undergraduate adult education and extra-mural studies students. Method: Eighty six students participated in the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Apart from that, when the two groups were compared using GLMM, the intervention group experienced a significantly higher reduction of anxiety scores. These findings on reduced anxiety levels among adolescents following health education intervention were supported by previous international RCT studies [37][38][39]. The findings of this study were consistent with the most similar parallel cluster RCT study in Malaysia, which analysed the effect of health education on reducing anxiety among school-aged students at immediately post-intervention and three-month follow-up [40].…”
Section: Discussionsupporting
confidence: 90%
“…Apart from that, when the two groups were compared using GLMM, the intervention group experienced a significantly higher reduction of anxiety scores. These findings on reduced anxiety levels among adolescents following health education intervention were supported by previous international RCT studies [37][38][39]. The findings of this study were consistent with the most similar parallel cluster RCT study in Malaysia, which analysed the effect of health education on reducing anxiety among school-aged students at immediately post-intervention and three-month follow-up [40].…”
Section: Discussionsupporting
confidence: 90%
“…[5] Another cross-sectional study found that depression was prevalent in 28.8% of university students. [6] A previous study also found that among 1359 university students, 19.6% reported severe depressive symptoms. [7] The caseload of moderate to severe depression was 25.2% in a cross-sectional survey of 820 Nigerian university students.…”
Section: Introductionmentioning
confidence: 91%
“…While researchers have studied the significance of psychological interventions (e.g. rational emotive behavior therapy-REBT) in treating depression in other student and non-student groups, [17][18][19] no evidence of such interventions exists among pre-service adult education teachers. In order to determine if a treatment model of REBT can be effective in treating depression among pre-service adult education teachers, this research was conducted.…”
Section: Introductionmentioning
confidence: 99%